Social work capstone projects demonstrating professional competencies through applied research - Poulin, John E.; Ingersoll, Travis Sky; Kauffman, Stephan (New York Springer Publishing, 2022)
"This textbook targets BSW and MSW programs that require students to conduct capstone research projects and/or research projects tied to their field placements. The focus is on designing, implementing and reporting research projects aimed at improving programs and services. Although this book reviews some content typically provided in social work research and/or generalist practice courses it is not intended to compete with existing social work research or practice textbooks. This book is the only one available in social work that focuses on student's capstone research projects"--
Includes bibliographical references and index.
Keywords: Social work education; Social service -- Methodology; Social service -- Research